Normative contexts and moral decision - Philips, Michael (Journal of business ethics, 1985)
This paper attempts to explain the significance of the ‘ideologies’ — or ‘middle-level’ normative discourse — described by Kenneth Goodpaster in his paper ‘Business Ethics, Ideology, and the Naturalistic Fallacy’. It is argued that the propositions constitutive of this discourse are not invokable moral principles (i.e. principles which generate solutions to actual moral problems). Rather, they are characterizations of the normative contexts in which moral decisions are made. As such, they place limits on the ways in which the abstract moral principles of traditional moral theory may be applied or interpreted in making real-life moral decisions.